Cascade Synthesis of Luminescent Difluoroboron Diketonate Compounds for Room‐Temperature Organic Afterglow Materials. Issue 21 (13th August 2022) - Li, Junbo; Wang, Xuepu; Zhao, Xiaoya; Chen, Xuefeng; Ding, Shuhui; Wu, Minjian; Zhang, Kaka
Comprehensive Summary: Difluoroboron β‐diketonate (BF2 bdk) compounds represent an important class of luminescent materials, whereas their synthesis requires multiple steps, which restrict their application in diverse fields. Here we report a cascade reaction to prepare BF2 bdk from aromatic ketones, carboxylic acids, trifluoroacetic anhydride and boron trifluoride diethyl etherate. The cascade reaction is very simple and straightforward to produce BF2 bdk with desired functional groups in reasonable isolation yields. Further, when some specific BF2 bdk compounds are used as luminescent dopants, organic room‐temperature phosphorescence with lifetimes >1.0 s and intense afterglow under ambient conditions can be achieved with the assistance by suitable organic matrices. The dopant‐matrix materials exhibit excellent processability into desired patterns and large‐area panels, and function as efficient donors of excited state energy transfer for the fabrication of red afterglow materials. The materials can be processed into aqueous afterglow dispersion that displays unique property of escaping the interference from strong fluorescence background. Abstract : Difluoroboron β‐diketonate (BF2 bdk) compounds represent an important class of luminescent materials, whereas their synthesis requires multiple steps, which restrict their application in diverse fields. This study presents a cascade reaction to prepare BF2 bdk from aromatic ketones, carboxylic acids, trifluoroacetic anhydride and boron trifluoride diethyl etherate. The obtained BF2 bdk compounds, upon doping into suitable organic matrices, have been found to display intense organic afterglow properties under ambient conditions.